Social action and education for citizenship in Scotland - Fyfe, Ian (Groupwork, 2013)
The idea of active citizenship has become a key element in the ongoing democratic renewal of Scotland. The policy priorities of the recently devolved Scottish Government have placed a fresh focus on the role and agency of young people as the future political generation. This paper draws on practice-based experience of a pilot programme of education for citizenship engaging groups of students within a special school setting. The groupwork approach was informed by the social action model of practice that supported the participants in a critical analysis of their own interests, concerns and needs. The programme provided young people with an arena for collective political expression and a vehicle for the exploration of their role as active citizens. The outcomes of the learning process included the acquisition of the base knowledge and core skills necessary for their effective participation as well as the development of a collective agenda for change. The findings of the work point towards the possibilities for the development of a complementary curriculum approach based upon the lived experiences of the young people themselves.